Portrayal and Existence of Islamic Majapahit: Viewed from the Archaeological Remains at Trowulan Site Mojokerto Regency, East Java - Eriawati, Yusmaini (Jurnal Sociohumaniora Kodepena (JSK), 2023)
Majapahit is known as a big kingdom in Indonesia during 14th – early 16th centuries AD with Hindu-Buddhist background. However archaeological evidences have shown the presence of another religion, which is Islam. This paper presents portrayal and existence of Islam in Majapahit based on the archaeological remains at the site of Trowulan and its surroundings, and outside Java, as well as textual data (Chinese and European written sources, manuscript, and babad). Results of researches show a portrayal of Islam in Majapahit, in which the art and culture still have Hindu-Buddhist elements in the concepts about death, and gave rise to Majapahit-style of Islam. The presence of Islam during the Majapahit era existed for a long period of time (from the ruling period jaaccepted open heartedly, and was embraced not only by visitors (Chinese, Arabs, Persian) but also the local community of Majapahit, particularly the aristocrats or rulers who were the descendants of Majapahit kings.